Recent Developments in Toxicology Study - Jana, Soumya Kanti; Chakravarty, Lopamudra (Asian Journal of Pharmaceutical Research and Development, 2023)
The story of toxicology began in the primitive age where our ancestors were fighting the battle of survival, they recognized the poisonous plants and extracted the poison which they used to survive. That was just the beginning and by the 1500BC people already marked opium, hemlock and some certain metals as the dangerous poisonous substances. Toxicology was at first developed as the study of poisons but through the development it is now the study of adverse effect of chemical agents on living organism. The key of any development is to overcome the setbacks and the toxicological development was no exception. Various setbacks appeared through the ages like sulfanilamide catastrophe, irrational use of animals in toxicity study, cross species differences, financial exposures etc. All of these setbacks pushed the human beings to the urge of developing new methodology, technology for the toxicology study and as results various in-vitro study methods, toxicogenomics, toxicoproteomics study emerged.